2019
DOI: 10.1155/2019/3720127
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indexes Design for Online Monitoring Polymer Injection Molding

Abstract: Quality control is a crucial issue in the injection molding process with target of obtaining a high yield rate and reducing production cost. Consequently, effective methods for monitoring the injection conditions (e.g., pressure, velocity, and temperature) in real-time and adjusting these conditions adaptively as required to ensure a consistent part quality are essential. This study proposes a quality index based on the clamping force increment during the injection cycle, as determined by four strain gauges at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Cavity pressure has been found to be a reliable process indicator in injection molding, for both part quality and process monitoring [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, it has been found to provide real-time detection of part and process deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Cavity pressure has been found to be a reliable process indicator in injection molding, for both part quality and process monitoring [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, it has been found to provide real-time detection of part and process deviation.…”
Section: Introductionmentioning
confidence: 99%
“…This index is related to the overall pressure characteristics of the polymer melt during the injection molding process. Deviations may reflect changes in part quality, particularly weight changes [ 30 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [15,16] investigated the effect of mold separation on molded part quality through a precise linear displacement transducer installed outside the mold plates, and found that the maximum mold separation occurring in the V/P switchover is highly correlated with part weight. Chen et al [17] conducted an experimental verification of several quality indexes, including peak pressure, viscosity extracted pressure profiles from the system, the nozzle, and the cavity, as well as the clamping force increment extracted from the tie-bar elongation profile. They found that these quality indexes, especially the clamping force increment index, have a strong correlation with the part quality.…”
Section: Literature Reviewmentioning
confidence: 99%